2006
DOI: 10.1590/s0103-90162006000300012
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of organic greenhouse lettuce production in Turkey

Abstract: Health issues and environmental concerns have drawn the attention to organic agriculture aiming to protect the natural balance and to produce without damaging the environment. This study aims determining economic feasibility of organic greenhouse lettuce (Lactuca sativa L.) in an on farm trial, to foster organic greenhouse vegetable production in the preservation area of Tahtali Dam, projected as the sole water resource of Izmir, Turkey's third largest. A 384 m 2 greenhouse, constructed of galvanized metal tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…There are some studies in Turkey favoring organic agriculture. For example, Engindeniz (2006) found that organic lettuce production is an economically reasonable alternative production system for farmers, although the average total costs in this system are higher than th at of conventional farms. In the long run, the costs of organic agriculture are expected to go down as total production and sales increase, and organic production systems become more productive.…”
Section: Ismet Boz Cevahir Kaynakci Possibilities Of Improving Organmentioning
confidence: 99%
“…There are some studies in Turkey favoring organic agriculture. For example, Engindeniz (2006) found that organic lettuce production is an economically reasonable alternative production system for farmers, although the average total costs in this system are higher than th at of conventional farms. In the long run, the costs of organic agriculture are expected to go down as total production and sales increase, and organic production systems become more productive.…”
Section: Ismet Boz Cevahir Kaynakci Possibilities Of Improving Organmentioning
confidence: 99%
“…Mayberry (2000) reported that in conventional production of lettuce 8.84% of total costs are fixed costs. On the other hand, Engindeniz and Tuzel (2006) stated a higher share of fixed costs in total costs of organic production of lettuce in a greenhouse. Depending on the fertilization treatment, fixed costs represented 16.3-17.4 % of total costs.…”
Section: Costsmentioning
confidence: 99%
“…In this study, administrative costs were estimated to be 3% of total variable costs. This method was applied in most of the previous studies (Engindeniz & Tüzel, 2002;Engindeniz, 2004;Tüzel et al, 2005;Engindeniz & Tüzel, 2006;. Depreciation for initial investment was estimated using the straight-line method (Penson et al, 2002;Lazol, 2007).…”
Section: Economic Analysismentioning
confidence: 99%